Triggering Presupposition in Selena Gomez's Interview at Signal 2023 - Anak Agung Istri Wulan Sukmawati; Ni Luh Nyoman Seri Malini; I Gusti Ngurah Parthama (Peneliti.net, 2026)
This study explores how presuppositions are triggered in Selena Gomez’s interview at signal 2023 has been uploaded on YouTube, focusing on how these implicit meanings contribute to the motivational and emotional tone of her responses. The research applies Yule’s (1996) theory of presupposition, which classifies six types of triggers: existential, factive, lexical, structural, non-factive, and counterfactual. A descriptive qualitative method was employed, with data collected from the verified transcript of the interview. The analysis identified 15 presuppositions, with existential and factive types occurring most frequently. These dominant types reveal how Gomez uses personal experiences, emotions, and reflections to convey sincerity and inspire her audience implicitly. The findings indicate that presupposition functions not only as a pragmatic device but also as a rhetorical strategy that strengthens authenticity and engagement in natural conversation. Thus, this study affirms that presuppositions play a vital role in constructing meaning and emotional connection within real-life interviews.